Water and the city: Valorising Guimarães water heritage for tourism - Ramazanova, Makhabbat (2020)
Water is the most important natural source of human existence and the main element of the socio-economic development of any industry. Water is an essential in meaningful experience of the visitors, who have an internal relation with this touristic resource as an attraction. As a cultural resource is associated with symbolic and artistic meanings. In urban areas where water is often ignored and its heritage elements are underestimated, the valorisation of its heritage elements and natural state is essential to create a safeguard and protection attitude towards this vital asset of life. To value is to recognise importance, to understand significance, to act towards conservation in both natural and cultural angles, particularly in cities where the conservation of water resources is critical and ignored in an urban development process. In this perspective, the present study attempts to analyse the water heritage state in the historical city Guimarães with the aim to valorise the water heritage resources linked to traditions and local historical narratives. Giving significance to those historical assets, aims to promote sustainable use and sustainable visit development. In this context, it is important to understand the residents’ view about the water presence in Guimarães, to understand the local opinion about the valorisation of water heritage for tourism and to understand what could the city do in conservation and the implementation of sustainable attitude related with this vital resource.